The Effect of Taxpayer Awareness and Sanctions on Land and Building Taxpayer Compliance - Hanny Williyany; Ayi Srie Yuniawati (LPPM Universitas Sebelas April, 2019)
The background of writing this thesis is the lack of awareness and knowledge of land and building tax sanctions in South Sumedang District. The object of research is South Sumedang District. This study aims to determine how the influence of awareness and sanctions on the compliance of land and building taxpayers in South Sumedang District. The method used in this research is quantitative method. The data collection technique used a questionnaire with a total of 100 samples. The method of determining the sample uses probability sampling using the Slovin formula. The results of this study indicate that the taxpayer awareness variable has a significant effect on land and building taxpayer compliance and has a significant effect with a Tcount of 3.050 > Ttable 1985. The sanctions variable has a significant effect on the compliance of the Land and Building taxpayers and has an effect with Tcount 3.081 > Ttable 1.985 and simultaneously the taxpayer awareness and sanctions variables have a significant effect on the compliance of land and building taxpayers in South Sumedang District and have an effect with Fcount 6.230>Ftable 3.091 and give an effect of 43.1% and 100%- 43.1% = 56.9% influenced by other factors that are not included in the research variables